Middleton, Nicos - (:unkn) unknown (My University, 2026)
Nicos Middleton, BSc Statistics and Operational Research (UCL, 1997), MSc Health Care Decision Analysis (LSE and LSHTM, 1998) and PhD Epidemiology (University of Bristol, 2004) joined the Department of Nursing, School of Health Sciences, Cyprus University of Technology in 2009 as Assistant Professor in Health Sciences Research Methodology and Biostatistics. Currently, he is Associate Professor (since Nov 2014), Head of Department and Director of Doctoral programme. He has served as member of the CUT Senate for two years and he is a member of the University Committee for Postgraduate Studies. Previous affiliations include the Department of Social Medicine, University of Bristol (Lecturer in Medical Statistics, 2004-2005), the Harvard School of Public Health (postdoctoral research fellow, 2006-2008) and the Cyprus International Institute for Environmental and Public Health (visiting Lecturer, 2006-2008). His research interests fall within the sphere of chronic disease (e.g. asthma, cancer), mental health and geographical epidemiology, particularly with respect to population health inequalities and the social and physical environmental determinants of health. Currently, he is the scientific coordinator of the “BrEaST start in life” project (funded by EEA NGO Grants), a longitudinal study of mothers who gave birth in Cypriot maternity clinics in order to provide first-time indicators (initiation, exclusivity and duration) and determinants of breastfeeding (maternity clinic practices, self-efficacy, support from the social and work environment). Previously, he has been the Lead Statistician/ Epidemiologist in the largest epidemiological studies performed so far in Cyprus on childhood asthma and respiratory health (Dr P. Yiallouros, PI, Cyprus International Institute for Environmental and Public Health) while in the last 5 years he has been involved in a number of other research projects (funded by FP7, Cyprus RPF, MoH, and CUT internal funds). His research work has attracted considerable international attention, and more recently with regards to the potential adverse effects of long-range transport of Saharan dust on cardio-respiratory health, which several studies across Southern Europe have since replicated. Currently, his research team are aiming to develop a small-area composite index of socio-economic deprivation to document the social gradient in health across Cypriot communities. He was the main PhD advisor of Dr Ourania Kolokotroni (title awarded 2015) and Dr Christiana Nicolaou (title awarded 2015). Currently, he is supervising two more PhD candidates and is a member of several more PhD and MSc advising committees in CUT and elsewhere. Now, featuring more than 1300 citations in the literature (h-index=19, i10-index=23), work he authored/co-authored have been published in high impact journals, and disseminated widely at local and international conferences (IEA, ERS, EuroEpi, EUPHA). His teaching experience covers a broad range of subjects, including Health Research Methodology, Epidemiology, Biostatistics, Evidence-based practice, Systematic reviews and meta-analysis, Scientific writing and presentation skills, at undergraduate, postgraduate and doctoral level. In September 2015 he was appointed as Government Representative in the Board of Directors of the Health Insurance Organization.
Keywords: Epidemiology; Public Health; nursing; multidisciplinary; health; Social Determinants of Health; Health Inequalities; Health Policy; Health Services Research; Health Research Methodology